2014
DOI: 10.1182/blood-2014-01-453134
|View full text |Cite
|
Sign up to set email alerts
|

Src family kinases: at the forefront of platelet activation

Abstract: Src family kinases (SFKs) play a central role in mediating the rapid response of platelets to vascular injury. They transmit activation signals from a diverse repertoire of platelet surface receptors, including the integrin αIIbβ3, the immunoreceptor tyrosine–based activation motif–containing collagen receptor complex GPVI-FcR γ-chain, and the von Willebrand factor receptor complex GPIb-IX-V, which are essential for thrombus growth and stability. Ligand-mediated clustering of these receptors triggers an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
221
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(234 citation statements)
references
References 101 publications
5
221
2
6
Order By: Relevance
“…It was shown that Gαi-receptors can activate such SFK as Lyn [55], which results in PLCγ and PI3K activation [6,56,57]. Furthermore, SFK inhibitors can abolish platelet aggregation [55].…”
Section: Model Assumptionsmentioning
confidence: 98%
“…It was shown that Gαi-receptors can activate such SFK as Lyn [55], which results in PLCγ and PI3K activation [6,56,57]. Furthermore, SFK inhibitors can abolish platelet aggregation [55].…”
Section: Model Assumptionsmentioning
confidence: 98%
“…55 Further work using mouse platelets singly or doubly deficient in SFKs has revealed both unique and overlapping roles for individual family members, with c-Src and Lyn proving to be the dominant effectors of a IIb b 3 outside-in driven responses, although Lyn appears to hold both positive and negative roles. 11,56,57 Although cSrc, Lyn, and Fyn are the more highly expressed SFKs in platelets, 56,[58][59][60] differences in the relative abundance of these kinases between mouse and human platelets mean an element of caution should be applied when interpreting mouse platelets as a model for human platelet SFK signaling; historical SFK inhibitors are also likely to have off-target effects.…”
Section: Src-family Kinasesmentioning
confidence: 99%
“…It is known that there are 7–8 members of SFKs in human platelets and neutrophils [110, 111]. Inhibition of SFKs with PP2, a broad-spectrum SFK inhibitor, partially impaired thrombin-mediated P-selectin exposure and αIIbβ3 integrin activation [112].…”
Section: Molecules Regulating the Function Of Surface Receptors Requimentioning
confidence: 99%